Cuticular hydrocarbons for the identification and geographic assignment of empty puparia of forensically important flies - Moore, Hannah; Lutz, Lena; Bernhardt, Victoria; Drijfhout, Falko P.; Cody, Robert B.; Amendt, Jens (Springer, 2022)
Research in social insects has shown that hydrocarbons on their cuticle are species-specific. This has also been proven for Diptera and is a promising tool for identifying important fly taxa in Forensic Entomology. Sometimes the empty puparia, in which the metamorphosis to the adult fly has taken place, can be the most useful entomological evidence at the crime scene. However, so far, they are used with little profit in criminal investigations due to the difficulties of reliably discriminate among different species. We analysed the CHC chemical profiles of empty puparia from seven forensically important blow flies Calliphora vicina, Chrysomya albiceps, Lucilia caesar, Lucilia sericata, Lucilia silvarum, Protophormia terraenovae, Phormia regina and the flesh fly Sarcophaga caerulescens. The aim was to use their profiles for identification but also investigate geographical differences by comparing profiles of the same species (here: C. vicina and L. sericata) from different regions. The cuticular hydrocarbons were extracted with hexane and analysed using gas chromatography-mass spectrometry. Our results reveal distinguishing differences within the cuticular hydrocarbon profiles allowing for identification of all analysed species. There were also differences shown in the profiles of C. vicina from Germany, Spain, Norway and England, indicating that geographical locations can be determined from this chemical analysis. Differences in L. sericata, sampled from England and two locations in Germany, were less pronounced, but there was even some indication that it may be possible to distinguish populations within Germany that are about 70 km apart from one another.
Keywords: Cuticular hydrocarbons; GC–MS; PCA; Calliphoridae; Empty puparia; Forensic entomology